The Effectiveness of Collaborative Writing Strategy (CWS) in Writing Lesson Regarded to The Students’ Creativity - Kiky Soraya (Lingua Cultura, 2016)
This study is aimed at finding out what appropriate methods to be usedin writing lesson seen from the students’ creativity especially for studentswho have high creativityand low creativity. This study used quasi experimental research. The population of the research was the eighth grade of a Junior High School in Wonosari in the academic year of 2013/2014. The sampling technique used was cluster random sampling. The sample in this study was 64 students covering 32 students of E as experimental class and 32 students of C as control class. The data or the students’ writing scores were analyzed in terms of their frequency distribution, normality, homogeneity, then ANOVA and Tuckey tests to test the research hypotheses. Based on the result, the research findings are: CWS is more effective than MWS in writing lesson; the high creativity students produced better writing rather than the low creativity student; and the interaction of teaching methods and the students’ creativity is existing in this writing lesson. In short, Collaborative Writing Strategy (CWS) is effective to teach writing for the eighth grade of a Junior High School in Wonosari, Gunungkidul. Then, the research result implies that it is better for the teachers to apply CWS in teaching and learning process of writing, to improve the students’ writing achievement, CWS needs to be used in the classroom activities, then future research can conduct the similar research with different sample and different students’ condition.